Evaluation of the heat and energy performance of a datacenter by a new efficiency index: Energy Usage Effectiveness Design - EUED - Santos, Alexandre F. (2019)
Data Centers are growing steadily worldwide and they are expected to continue on growing up to 53% in 2020. Due to this growth the energy efficiency in this type of building is essential. There are methodologies to measure this efficiency; one example is PUE (Power Usage Effectiveness). The unit suggested for measuring efficiency at the design stage would be the EUED (Energy Usage Efficiency Design) with this will be used data to use "free cooling" and adiabatic system in some cases, a comparison will be made only considering the equipment in the worst situation. It also uses the study of enthalpy utilization as a new methodology to obtain the results. By doing so, differences were found, between cities than 1.21% of São Paulo in relation to Curitiba and 10.61% of Rio de Janeiro in relation to Curitiba. The indices obtained by applying the EUED index were 1.245 kW.kW- 1 for Curitiba, 1.260 kW.kW-1 for São Paulo and 1.377 kW.kW-1 for Rio de Janeiro, respectively, giving a difference of 16.86% for Curitiba of 16.19% for São Paulo and 10.31% for Rio de Janeiro in relation to PUE COA (Power Usage Effectiveness Constant Outdoor Air).